Persepsi Mahasiswa Pengguna IPhone sebagai Eksistensi Diri di Universitas Medan Area - Purnama, Shinta Wulan; Yolanda, Agnita; Andary, Ria Wuri (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
Students' lifestyles tend to be consumptive, such as purchasing items such as smartphones which become their daily needs and are considered to be able to follow their existence. The purpose of this research is to find out how students perceive Iphone users as their own existence. The problem focuses on the perception of Psychology students at Medan Area University who use Iphone as a means of self-existence. In order to approach this problem, this research uses perception theory according to Jalaludin Rakhmat (2011). The method used is a qualitative method with a descriptive approach. Using purposive techniques, there were 4 informants. Data was collected through observation, in-depth interviews and documentation and analyzed qualitatively. This study concludes that self-existence has restored students' perceptions of objects to show who they are based on the choice of smartphone brand they use, such as the Iphone.